An Investigation on Dislocation Density in Cold-Rolled Copper Using Electrochemical Impedance Spectroscopy. (25th March 2013) - Rafiee, Elyas; Farzam, Mansour; Golozar, Mohammad Ali; Ashrafi, Ali
Abstract : Variation of electrochemical impedance with dislocation density was investigated using electrochemical impedance spectroscopy (EIS). For this purpose, EIS measurements were carried out on 10, 20, 30, 40, and 50% cold-rolled commercially pure copper in 0.1 M NaCl (pH = 2) solution. Nyquist plots illustrated that the electrochemical reactions are controlled by both charge transfer and diffusion process. Increasing dislocation density, the magnitude of electrochemical impedance of samples was decreased. Decreasing magnitude of impedance at intermediate frequencies indicated increasing double-layer capacitance. Charge transfer resistance decreased from value 329.6 Ωcm 2 for annealed sample to 186.3 Ωcm 2 for sample with maximum dislocation density (1.72 × 10 15  m − 2 ). Phase angles were lower for samples that contained more dislocation density, indicating more tendencies to loss of electrons and releasing atoms into electrolyte.